Prevalence, risk assessment, and predictors of osteoporosis among chronic obstructive pulmonary disease patients - Ahmad Naoras Bitar; Syed Azhar Syed Sulaiman; Irfhan Ali Bin Hyder Ali; Amer Hayat Khan (Wolters Kluwer Medknow Publications, 2021)
The link between chronic obstructive pulmonary disease (COPD) and osteoporosis is unclear and yet to be understood. The study goals were to detect the prevalence of osteoporosis and investigate its predictors among COPD patients. This is a longitudinal study conducted in a tertiary care setting. During the study, patients' bone mineral density was checked, pulmonary parameters were recorded, and a risk assessment tool was validated. Based on T-score, more than 50% of subjects were osteoporotic. Spirometric parameters were significantly lower among osteoporotic patients. For the risk assessment tool, a cutoff point of 34 made the optimum balance between sensitivity and specificity (0.867 and 0.087, respectively) with a generated area under the curve of 0.934. Severe COPD patients were four times at higher risk of getting osteoporosis, forced expiratory volume (FEV) % predicted, and FEV/forced vital capacity was inversely related to the risk of osteoporosis. Patients with severe dyspnea had twice the risk of getting osteoporosis. Osteoporosis was prevalent among COPD patients, and severe COPD patients were at higher risk of getting osteoporosis.